2014
DOI: 10.1007/s11606-014-2809-x
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Awareness and Control Among Young Adults in the National Longitudinal Study of Adolescent Health

Abstract: BACKGROUND: Young adults are less likely than older adults to be aware they have hypertension or to be treated for hypertension. OBJECTIVE: To describe rates of hypertension awareness and control in a cohort of young adults and understand the impact of health insurance, utilization of preventive care, and self-perception of health on rates of hypertension awareness and control in this age group. DESIGN AND PARTICIPANTS: Cross-sectional study of 13,512 young adults participating in Wave IV of the National Longi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
73
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 20 publications
8
73
1
2
Order By: Relevance
“…These results were consistent with previous NHANES reports, 33, 34 as well as with results from a cross-sectional study of young adults aged 24 to 32 years from the National Longitudinal Study of Adolescent Health, which found that hypertension awareness was about two fold higher in young adults who had seen a provider for routine health care in the past two years. 35 Taken together, these findings suggest that efforts to improve blood pressure control among young adults, particularly men, should focus on raising awareness, improving screening strategy, and advancing follow-up and subsequent linkage to care. 4, 35 With implementation of the Affordable Care Act, the rate of insurance in U.S. adults aged 19–25 years old increased by over 10% since 2010, representing an increase of about 5.7 million young adults with access to a regular source of medical care, and potentially, prevention programs.…”
Section: Discussionmentioning
confidence: 95%
“…These results were consistent with previous NHANES reports, 33, 34 as well as with results from a cross-sectional study of young adults aged 24 to 32 years from the National Longitudinal Study of Adolescent Health, which found that hypertension awareness was about two fold higher in young adults who had seen a provider for routine health care in the past two years. 35 Taken together, these findings suggest that efforts to improve blood pressure control among young adults, particularly men, should focus on raising awareness, improving screening strategy, and advancing follow-up and subsequent linkage to care. 4, 35 With implementation of the Affordable Care Act, the rate of insurance in U.S. adults aged 19–25 years old increased by over 10% since 2010, representing an increase of about 5.7 million young adults with access to a regular source of medical care, and potentially, prevention programs.…”
Section: Discussionmentioning
confidence: 95%
“…The prevalence of systemic arterial hypertension (AH) continues to rise, especially in young adults [2]: in the United States it has reached 19% in 2008 in the 24-32 age group, according to the Add Health study [3]. The problem of the increased blood pressure becomes also conside rable among adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings have important public health relevance for young adults because recent evidence suggests that development of elevated BP before the age of 45 years is associated with significantly higher risks of cardiovascular death later in life compared with those who develop hypertension later in life 37. Rates of hypertension in young adults are increasing, and rates of hypertension awareness and control are lowest in this group 38. As highlighted in several other recent publications, targeting elevated BP and implementing lifestyle interventions to reduce BP in early adulthood may be an important strategy to prevent cardiovascular disease later in life 13, 39.…”
Section: Discussionmentioning
confidence: 60%